Renal resistive index: a new reversible tool for the early diagnosis and evaluation of organ perfusion in critically ill patients: a case report - Antonio Anile; Silvia Ferrario; Lorena Campanello; Maria Antonietta Orban; Giacomo Castiglione (The Ultrasound Journal, 2019)
Abstract Background We reported a case of early detection of peripheral hypoperfusion trough the evaluation of a new index in intensive care: Renal Doppler Resistive Index (RRI). Case presentation We admitted a 76-year-old man who underwent ileostomy and hernioplasty because of an intestinal occlusion due to obstructive strangulated right inguinal hernia. The post-operative period was characterised by hemodynamic instability and he needed an invasive hemodynamic monitoring, administration of vasopressors and continuous renal replacement therapy (CRRT). Then, hemodynamic stability was obtained and vasopressors interrupted. RRI was lower than 0.7. In the eleventh post-operative day, despite stable macrocirculatory parameters, we found increased values of RRI. An abdomen ultrasound first and then a CT scan revealed the presence of bleeding from the previous ileostomy. Hence, the patient immediately underwent another surgical operation. Conclusions RRI modification appears to be more precocious than any other hemodynamic, microcirculatory and metabolic parameter routinely used. RRI has been widely used to assess renal function in critically ill patients; now, we presume that RRI could represent a common and useful tool to manage target therapy in critical condition.